Impact of postoperative complications on disease recurrence and long‐term survival following oesophagogastric cancer resection. Issue 1 (23rd December 2019) - Saunders, J. H.; Yanni, F.; Dorrington, M. S.; Bowman, C. R.; Vohra, R. S.; Parsons, S. L.; ,
Abstract : Background: Postoperative complications after resection of oesophagogastric carcinoma can result in considerable early morbidity and mortality. However, the long‐term effects on survival are less clear. Methods: All patients undergoing intentionally curative resection for oesophageal or gastric cancer between 2006 and 2016 were selected from an institutional database. Patients were categorized by complication severity according to the Clavien–Dindo classification (grades 0–V). Complications were defined according to an international consensus statement. The effect of leak and severe non‐leak‐related complications on overall survival, recurrence and disease‐free survival was assessed using Kaplan–Meier analyses to evaluate differences between groups. All factors significantly associated with survival in univariable analysis were entered into a Cox multivariable regression model with stepwise elimination. Results: Some 1100 patients were included, with a median age of 69 (range 28–92) years; 48·1 per cent had stage III disease and cancer recurred in 428 patients (38·9 per cent). Complications of grade III or higher occurred in 244 patients (22·2 per cent). The most common complications were pulmonary (29·9 per cent), with a 13·0 per cent incidence of pneumonia. Rates of atrial dysrhythmia and anastomotic leak were 10·0 and 9·6 per cent respectively. Patients with a grade III–IV leak did not have significantly reduced overall survival compared with those who had grade 0–I complications. However, patients with grade III–IV non‐leak‐related complications had reduced median overall survival (19·7 versus 42·7 months; P < 0·001) and disease‐free survival (18·4 versus 36·4 months; P < 0·001). Cox regression analysis identified age, tumour stage, resection margin and grade III–IV non‐leak‐related complications as independent predictors of poor overall and disease‐free survival. Conclusion: Beyond the acute postoperative period, anastomotic leak does not adversely affect survival, however, other severe postoperative complications do reduce long‐term overall and disease‐free survival. Abstract : Long‐term follow‐up of patients undergoing oesophagogastric cancer resection showed that it is severe non‐leak‐related complications, rather than anastomotic leaks, that significantly reduce overall and disease‐free survival. Bad news